1989
DOI: 10.1136/vr.125.7.143
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic drug resistance in the UK

Abstract: The term 'anthelmintic drug resistance' describes the heritable ability of some nematode parasites to survive treatment with anthelmintic drugs at the recommended therapeutic dose levels. Genes for resistance appear to be present in many of the important pathogenic nematodes of ruminants and horses. Under intensive management systems, where heavy reliance is placed on anthelmintic drugs for worm control, the selection of resistant genotypes may result in increased reports of the drugs failing to control the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…It has been observed that frequent usage of the same group of anthelmintic may result in the development of AR Barton, 1983;Coles, 1986;Waller, 1987;Taylor and Hunt, 1989). There is evidence that resistance develops more rapidly in regions where animals are dewormed regularly.…”
Section: Treatment Frequencymentioning
confidence: 94%
See 1 more Smart Citation
“…It has been observed that frequent usage of the same group of anthelmintic may result in the development of AR Barton, 1983;Coles, 1986;Waller, 1987;Taylor and Hunt, 1989). There is evidence that resistance develops more rapidly in regions where animals are dewormed regularly.…”
Section: Treatment Frequencymentioning
confidence: 94%
“…However, these actions result in the next helminth generation that consists almost completely of worms that survived therapy and, therefore, might contribute to the development of AR (Smith, 1990;Taylor and Hunt, 1989). For an example, Coles et al (1995) reported problem of AR in the helminths of sheep and goats on some small Greek islands which suffered from extended drought with, in contrast, no AR developed under similar management and deworming practices on the mainland.…”
Section: Targeting and Timing Of Mass Treatmentmentioning
confidence: 95%
“…It has long been recognised that treating ewes with anthelmintic at this time could be selective for anthelmintic resistance (Brunsdon et al 1983), especially in situations where nematode eggs passed by the ewes contribute signifi cantly to subsequent infection in lambs (Cawthorne and Whitehead 1983;Michel 1985;Taylor and Hunt 1989). In line with this, a modelling study by Leathwick et al (1995) showed that an anthelmintic treatment administered to adult ewes at lamb-docking time could be highly selective for resistance where it both pre-selected larval challenge to lambs and removed a source of unselected nematodes in refugia.…”
Section: High-risk Drenching and Stock-management Practicesmentioning
confidence: 99%
“…Chemotherapy using broad-spectrum anthelmintics remains the mainstay of control of GI nematodosis. Furthermore, the intensification of animal production systems has lead to increasing dependence on anthelmintics (Taylor and Hunt, 1989) and regular suppressive dosing of susceptible livestock has resulted in the development of resistance in GI nematodes throughout the world. In India, GI parasites are currently controlled by four major groups of anthelminticsbenzimidazoles, imidazothiazoles, salicylanides and avermectins.…”
Section: Introductionmentioning
confidence: 99%